UNIVERSITY WOMEN PERCEPTIONS ON MIGRATION (MERANTAU) AND WORKING OVERSEAS IN FACING ASEAN ECONOMIC COMMUNITY - Diniaty, Amirah; Kustati, Martin (ADDIN, 2016)
This descriptive study aims to explore university women’ perceptions on migration (Merantau) and working overseas in facing Asean Economic Community. 300 participants were identified using accidental random sampling. A Survey was used in this study. The finding showed that 69.4%) of respondents perceived that women have important roles in empowering their family economy. Then, 76.3% of them acknowledged that working overseas have provided significant improvement of economy for their family in the village.). 61.3% of respondents stated that they went abrad to continue their study to Post graduate programme. Meanwhile, there were only 35.3% of respondents declared that they wanted to work in Indonesia. Other 3% of respondents acknowledged that they wanted to become household and their husband shoud fulfill their daily life expenses. It also found that 85% of Minangkabau women could compete in having good career as compared with Women in ASEAN countries.74.3% declared that they must improve their softskill capabilities. Finally, there 85.3% of respondents declared that they were ready to face Asean Economic community (AEC).